Long term remote reactor power and fuel composition monitoring using antineutrinos - I. Alekseev; V. Belov; A. Bystryakov; M. Danilov; D. Filosofov; M. Fomina; P. Gorovtsov; Ye. Iusko; S. Kazartsev; V. Khvatov; S. Kiselev; A. Kobyakin; et al. (Physics Letters B)
Electron antineutrinos are emitted in the decay chains of the fission products inside a reactor core and could be used for remote monitoring of nuclear reactors. The DANSS detector is placed under the core of the 3.1 GW power reactor at the Kalinin Nuclear Power Plant (KNPP) and collects up to 5000 antineutrino events per day. DANSS measured changes of the reactor power by antineutrino counting rates over 7 years with 1.0% accuracy in one week periods. The fission fractions of four major isotopes for the reactor power calculations were provided by KNPP. The systematic uncertainty of this measurement is less than 0.8%. It is comparable to the accuracy of conventional methods of the reactor power measurements while it is based on completely different approach. For the first time the 239Pu and 235U fission fractions were reconstructed using antineutrino inverse beta-decay spectrum which is a completely new technique. This method was applied to the data from three reactor fuel campaigns (approximately 1.5 year each). The reconstructed fission fractions in about two-week measurements and the fission fractions provided by KNPP coincide within better than 3% accuracy. This provides confidence in both completely different approaches of the fission fraction determination.